PENGUATAN PENDIDIKAN TOLERANSI SEJAK USIA DINI (Menanamkan Nilai-nilai Toleransi Dalam Pluralisme Beragama Pada Pendidikan Anak Usia Dini (PAUD) Di Kabupaten Tulungagung Tahun 2010) - Zaini Zaini (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2010)
Many analysts and observers mention of early "The Golden Age" of the young age is highly effective embedded multi-dimensional education golden times that never happen again on the same occasion throughout human lifetime. What education can be given to children by parents, mother, father and educator will help shape the character and personality of the children. Character and personality are formed on the education of children is fundamental education that the can color the whole nature and lifestyle before it can be influenced by factors other than friends, the environment and conditions in which the child located. The more mature the child will be more complex, also influence which appear later. so that value of awareness and the values of honesty, mutual respect, mutual respect, esprit de corps, mutual giving and helping the others with no view his of the status and color of her dress as a manifestation of the values of tolerance and instilled a decent strengthened since early Childhood